1994
DOI: 10.1016/0169-5150(94)00008-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of official development assistance on agricultural growth, savings and agricultural imports

Abstract: This paper explores the links between development assistance, agricultural output growth and imports in 56 developing economies over the period [1974][1975][1976][1977][1978][1979][1980][1981][1982][1983][1984][1985][1986][1987][1988][1989][1990]. Thc empirical model treats agricultural growth and imports, savings and aid as endogenous. The analysis also accounts for differences in macroeconomic policies. The results show that aid had a positive impact on agricultural growth. A robust relationship exits betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
2
10
0
2
Order By: Relevance
“…In addition, aid seems to be less effective in countries where the fiscal deficit and external debt were high. Another study by Kherallah et al (), using a simultaneous equation model for a panel data of 56 developing countries over the period of 1974–1990, found a positive relationship between foreign aid and agricultural growth. Their study demonstrated that a 1% increase in foreign aid led to a 0.75% increase in agricultural growth rate.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, aid seems to be less effective in countries where the fiscal deficit and external debt were high. Another study by Kherallah et al (), using a simultaneous equation model for a panel data of 56 developing countries over the period of 1974–1990, found a positive relationship between foreign aid and agricultural growth. Their study demonstrated that a 1% increase in foreign aid led to a 0.75% increase in agricultural growth rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the impact of the total aid was positive, while the impact of gross domestic saving was negative for the large group, according to the auteurs, this result is due to the allocation or redeployment of domestic savings to food production (FP) activities in these countries. However, all these studies (Norton et al (); Kherallah et al (); Aboagyea and Gunjal, ()) suffered from the unavailability of data regarding agricultural aid in specific. Therefore, the authors used total aid as the main explanatory variable without distinguishing between aid intended for the agricultural sector and other sectors of ODA.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations